Diversification reactions of γ-silyl allenyl esters: selective conversion to all-carbon quaternary centers and γ-allene dicarbinols. Issue 37 (24th April 2017) - Jana, Susovan; Roy, Animesh; Lepore, Salvatore D.
Abstract : Taking advantage of an organosilicon auxiliary, allenes are selectively converted under mild conditions to either all-carbon quaternary centers (including via SN Ar) or allene dicarbinols depending on the electrophile. Abstract : The unique reactivity of γ-silyl allenyl esters is described. Taking advantage of the silyl group as a fluoride acceptor, these allenoates readily underwent addition to a variety of electrophiles to selectively yield products with all-carbon quaternary centers or allenoate dicarbinols. These dicarbinols were subsequently converted to novel highly substituted 6-hydro-2-pyrones.